(untitled) (Abibisem: Journal of African Culture and Civilization, 2011)
The traditional Yoruba society in the south-western part of Nigeria is essentially polygamous. Even though oral traditions of the people indicate that in the earliest times, the Yoruba cherished monogamy, by the time of the advent of the Christian Missions in general, and Baptist Mission in particular, the social custom of polygamy had been well- rooted in the people’s cultural life. The impression is often carried that the Baptist denomination in Nigeria is less strict on certain Christian religious observances such as the prohibition of polygamy when compared with some of its counterpart Protestant Churches. The evidence at our disposal reveals that this is an erroneous impression. Even though polygamists do attend Baptist Churches, as is the case in many other Christian churches, the Baptists did try to insist on monogamy, yet polygamy remained a very hard nut to crack. At any rate, the insistence of the Mission on maintaining its stand on monogamy was to effect a chink in the armour of Baptist expansion and growth in the Yoruba country.